Mitogenomic evidence of population differentiation of thorny skate, Amblyraja radiata , in the North Atlantic - John S. S. Denton; Jeff Kneebone; Lei Yang; Arve Lynghammar; David McElroy; Shannon Corrigan; Klara Jakobsdóttir; Carolyn Miri; Mark Simpson; Gavin J. P. Naylor (Journal of Fish Biology, 2024)
Management of thorny skate ( Amblyraja radiata ) in the Northwest Atlantic has posed a conservation dilemma for several decades due to the species' lack of response to strong conservation efforts in the US Gulf of Maine and the Canadian Scotian Shelf, confusion over the relationship between two reproductive size morphs of differing life histories that are sympatric in the Northwest Atlantic, and conflicting data on regional population connectivity throughout the species' broader range. To better assess potential A. radiata regional population differentiation and genetic links to life‐history variation, we analysed complete mitochondrial genome sequences from 527 specimens collected across the species' North Atlantic geographic range, with particular emphasis on the Northwest Atlantic region. A high level of genetic diversity was evident across the North Atlantic, but significant genetic differentiation was identified between specimens inhabiting the Northwest (Gulf of Maine and Newfoundland) and Northeast (Greenland, Iceland, North Sea, and Arctic Circle) Atlantic. In the Northwest Atlantic, significant differentiation between the Gulf of Maine and Newfoundland regions was revealed; however, the overall level of differentiation was very low. No genetic difference was identified between the large and small reproductive morphs. The results of this study advance our understanding of A. radiata population structure in the North Atlantic but do not resolve all the questions confounding our understanding of the species' biology and evolutionary history.